Measurement error : models, methods, and applications - Buonaccorsi, John P. (Boca Raton : CRC Press, 2010)
This book explains how to model measurement error, the effects of ignoring it, and how to correct for it. More applied than most books on measurement error, it describes basic models and methods, their uses in a range of application areas, and the associated terminology.
"A Chapman & Hall book."
Includes bibliographical references and indexes.
rua 15/05/13
Loans
Keywords: Error analysis (Mathematics)